2016
DOI: 10.3847/0004-637x/824/2/66
|View full text |Cite
|
Sign up to set email alerts
|

Nulling Data Reduction and on-Sky Performance of the Large Binocular Telescope Interferometer

Abstract: The Large Binocular Telescope Interferometer (LBTI) is a versatile instrument designed for highangular resolution and high-contrast infrared imaging (1.5-13 µm). In this paper, we focus on the mid-infrared (8-13 µm) nulling mode and present its theory of operation, data reduction, and onsky performance as of the end of the commissioning phase in March 2015. With an interferometric baseline of 14.4 meters, the LBTI nuller is specifically tuned to resolve the habitable zone of nearby main-sequence stars, where w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 53 publications
(47 reference statements)
1
71
0
Order By: Relevance
“…2 were photometric, but for specific systems it is possible to go deeper. Indeed, it might be possible to rule out a dust spot scenario using nulling interferometry (LBTI), which can go a few orders of magnitude deeper (Defrère et al 2016). However, LBTI requires bright stars, so this option would only be available for the nearest stars, which is the most interesting since this is where astrometric measurements are most sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 were photometric, but for specific systems it is possible to go deeper. Indeed, it might be possible to rule out a dust spot scenario using nulling interferometry (LBTI), which can go a few orders of magnitude deeper (Defrère et al 2016). However, LBTI requires bright stars, so this option would only be available for the nearest stars, which is the most interesting since this is where astrometric measurements are most sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…One way to explain this would be to show that the detection of the astrometric effect detected by Pravdo & Shaklan at 550-750 nm is wavelength dependent, for instance, in the far-IR or submillimetric regimes. We recommend observing it with SKA, when built, using astrometry or the Large Binocular Telescope Interferometer (LBTI, Defrère et al 2016) to look for warm dust.…”
Section: Chromaticitymentioning
confidence: 99%
“…24 Given the rapid sky variations, this procedure was found to perform better skysubtraction than alternatives such as the subtraction of a single frame from one of the adjacent nods, or the subtraction of an average of a median-combination of a fixed number of frames from both adjacent nods. At this point, the two-dimensional framesS were generated viã…”
Section: The Pipelinementioning
confidence: 99%
“…In a recent paper by Defrère et al [39], the LBTI team reported progress on the LBTI HOSTS program as of the end of the commissioning phase in the spring of 2015. This paper discussed the theory of operation of the LBTI as a nulling interferometer, data reduction methods, and on sky performance.…”
Section: Nulling Data Reduction and On-sky Performance Of Lbtimentioning
confidence: 99%